Investigating the functionality and constraints of urban pocket parks in Kuala Lumpur, Malaysia - Balai Kerishnan, Praveena (2020)
Pocket parks are also known as mini-parks or vest-pocket parks because it is an urban open space at a very small scale. These parks were introduced in dense city areas to contribute to the environment, social and health benefits. Despite this, few studies have tackled the functionality and constraint of use of these parks. Therefore, this study aims to investigate the usability pattern and constraints of pocket parks in a Malaysian context through survey. The survey consist of N=390 respondents comprising of pocket parks users and non-users aged between 18–60 years old. Overall, there are slightly more female than male using the pocket parks in Kuala Lumpur and most frequent age group was people between 18-30 years old. Most of the respondents visit the pocket parks ‘sometimes’; this is not surprising as 78% of them have to travel more than 300 m to reach the pocket parks nearest to them. Only 59 respondents use the park frequently; while 26 respondents have never used the parks. Most of the respondents visit the pocket parks by foot. Based on the statistical data, majority of the respondents prefer to visit the pocket parks in group; however, there was no significant positive association between the social factor companionship (group or alone) with the time spent in the parks. The statistical data also shows that the respondents prefer to spend longer time at the park in the evening and morning. Majority of the respondents use the pocket parks to ‘rest and reduce stress’. Respondents also use the parks ‘to take a shortcut’ and ‘to meet others’. Both male and female have similar motives of using the parks; however, of the 30 respondents that use the pocket parks as an ‘easiest access to nature’, 73.3% are female. Majority of the respondents stated ‘time’ as their major constraint in using the parks. Apart from ‘time’, respondents are also concerned about ‘crowded activity area’, ‘poor hygiene of other park users’ well as ‘safety aspect’. The presence of ‘homeless people’ living in the park area and the presence of ‘foreign workers using the park’ also limited the park functionality. The respondents opted for pocket parks that are ‘serene’, yet the survey documented other preferences such as food trucks/bazaar and suggestions for more activities such as zumba or aerobics. Food is one of the integral factors that brought more users to the pocket parks in Kuala Lumpur. This finding contradicts to small urban park users from other countries that visit the pocket parks as an opportunity to access nature for relaxation.